Clinical efficacy of systemic chemotherapy combined with radiofrequency ablation and microwave ablation for lung cancer: a comparative study. (1st January 2021) - Xu, Feng; Song, Jian; Lu, Yangyang; Wang, Jiang; Wang, Jing; Xiao, Haiyan; Li, Zhenzhen
Abstract: Objective: Local thermal ablation, a minimally invasive technique, has been widely used in clinical treatment of lung cancer. This study aimed to discuss the clinical efficacy of systemic chemotherapy combined with radiofrequency ablation (RFA) versus systemic chemotherapy combined with microwave ablation (MWA) in treating lung cancer. Methods: A retrospective analysis involving 124 lung cancer patients, who received RFA ( n = 68) and MWA ( n = 56) combined with systemic chemotherapy in Cangzhou People's Hospital from August 2017 to December 2019, was conducted. Before comparative analysis for therapeutic efficacy, the two groups of patients were matched with propensity score matching method at a ratio of 1:1. Indicators including progression-free survival (PFS), overall survival (OS), short-term efficacy, tumor marker level, local tumor control rate, and postoperative complications were comparatively analyzed. Results: There was no statistical difference in disease control rate and objective response rate (90.6% and 78.1% vs 93.8% and 84.4%) between RFA group and MWA group. The incidence of complications was 12.5% in RFA group and 18.8% in MWA group with no statistically significant difference. In addition, the local tumor control rate in MWA group (90.6%) was significantly higher than that in RFA group (78.1%). Regarding survival, a statistically significant difference was observed in median PFS of RFA and MWA groups (9.2 months vs 10.4 months, p < 0.05), while OS in two groups slightly varied. Conclusion: MWA was superior to RFA over local tumor control rate and PFS and showed great potential in lung cancer ablation treatment.